Quantum-Based Creative Generation Method for a Dancing Robot - Mei, Peng; Ding, GangYi; Jin, QianKun; Zhang, FuQuan; Jiao, YangFan (Frontiers in Neurorobotics, 2020)
In this paper, we propose a creative generation process model based on the quantum modeling simulation method. This model is mainly aimed at generating the running trajectory of the dancing robot and the execution plan of the dancing action. Firstly, we use digital twin technology to establish a data mapping between the robot and the computer simulation environment to realize the intelligent controllability of the robot's trajectory and dance movements in this paper. Secondly, we have conducted a lot of experiments and researches on information retrieval, information fidelity, and result evaluation. Moreover, a multi-level three-dimensional spatial quantum knowledge map (M-3DQKG) is constructed based on the coherence and entangled states of quantum modeling and simulation. Combined with dance videos, we use R-CNN to extract character bones and movement features to form a movement library. We use M-3DQKG to quickly retrieve information in the knowledge base, action library, and database, and then the system generates action models through the HED network. The system then renders scenes that match the action through the GANs network. Finally, the scene and dance movements are integrated, and the creative generation process is completed. This paper also proposes the creativity generation coefficient (CGC) to evaluate the results of creativity, combined with artificial brain electricity data (EEG) to assist in evaluating the degree of agreement between creativity and needs. This paper aims to realize the automation and intelligence of the creative generation process and improve the creative generation effect and usability of dance movements. Experiments show that this paper has significantly improved the efficiency of knowledge retrieval and the accuracy of knowledge acquisition, and can generate unique and practical dance moves. The robot trajectory is novel and changeable, which can meet the needs of dance performances in different scenes. The creative generation process of dancing robots combined with deep learning and quantum technology is a required field for future development, which can provide a considerable boost to the progress of human society.